HEALTH SERVICES VOCATIONAL SCHOOL STUDENTS’ KNOWLEDGE LEVELS OF ON PARASITIC DISEASES - Elasan, Sadi; Yürektürk, Şehriban; Ekici, Abdurrahman; Yılmaz, Hasan; Halidi, Ahmed Galip; Karakuş, Sinan; Yasul, Muhammed (My University, 2022)
In this study, it has been aimed to determine the knowledge level of the students of Van Yuzuncu Yıl University Health Services Vocational School, who will serve as the health personnel of the future, about parasitic diseases, prevention and control measures from these diseases. A total of 587 students, comprising 418 (71.2%) females and 169 (28.8%) males, studying at Van Yüzüncü Yıl University Health Services Vocational School, were included in the study. The questions in the questionnaire were arranged in three groups, as those about parasitic diseases, transmission routes of these diseases, and prevention and treatment. Cronbach alpha coefficients were calculated within the scope of the reliability analysis of the questionnaire questions. The Cronbach alpha values for the domains of Knowledge Level About Parasitic Diseases, Knowledge Level About the Transmission of Parasitic Diseases, and Knowledge Level About the Prevention and Treatment of Parasitic Diseases were determined as 0.647 (64.7%), 0.707 (70.7%), and 0.566 (56.6%), respectively. A statistically significant difference was found between the departments included in the study in terms of the level of knowledge about parasitic diseases (P < 0.05). A statistically significant difference was found between the departments in the evaluation made between the level of knowledge about the prevention and treatment of parasitic diseases and the personal characteristics of the students (P < 0.05). As the result, it was observed that the students participating in the study did not have sufficient knowledge about parasitic diseases.
Keywords: Parasite; Prevention; Health; Transmission